Respuesta :
Answer:
x³ + 4 x² + x - 6
Step-by-step explanation:
( x - 1 ) ( x + 2 ) ( x + 3 )
( x - 1 ) ( x + 2 ) = x² + 2 x - 1 x - 2 = x² + x - 2
( x² + x - 2 ) ( x + 3 ) = x³ + 3 x² + x² + 3 x - 2 x - 6 = x³ + 4 x² + x - 6
The expression (x-1)(x+2)(x+3) can be written as x³ + 4x² + x—6 after multiplication of the expression.
What is an expression?
It is defined as the combination of constants and variables with mathematical operators.
We have:
= (x-1)(x+2)(x+3)
After multiplying first and second terms:
[tex]\rm =\left(x^2+x-2\right)\left(x+3\right)[/tex]
Again multiplying:
[tex]\rm =x^3+4x^2+x-6[/tex]
Thus, the expression (x-1)(x+2)(x+3) can be written as x³ + 4x² + x—6 after multiplication of the expression.
Learn more about the expression here:
brainly.com/question/14083225
#SPJ2